[Rezension von: Apologetics in Africa : an introduction] - Pali, K. J. (Acta theologica, 2025)
The book "Apologetics in Africa: An introduction" by Ndereba, K.M. (ed.), (Bukuru: ACT and Langham Publishing, 2024), pp. 382, ISBN 9781839736629, is reviewed.